Gene Polymormisms and Prostate Cancer: A Systematic Review - Azizi, Faezeh; Soleimani, Mohammad; Hosseini, Seyed Yousef; Amini Nik, Saeid; Hosseini, Jalil (Archives of Men’s Health, 2018)
Introduction: The prostate is a gland that surrounds men’s urethra and helps to produce semen. In developed countries, prostate cancer (PCa.) is the second most common and lethal disease in men. Hereditary history of PCa. is a major contributor to this cancer? While a number of genetic and molecular changes have been reported in PCa, the general picture of the genetic aberrations is needed in Iranian population. Methods: In this study, a literature search from Jan. 2000 to June 2018 was performed through the PubMed, Google Scholar, Scopus, Web of Science, IranMedex, MEDLIB, IranDoc and Scientific Information databases using the keywords “genetic polymorphisms”, “prostate cancer”, “Iranian, and compare with regional and international population”. Results: The results revealed that several genome-wide association studies (such as rs2070744 and rs1799983 in the eNOS, rs243865 in the MMP2, rs1902023 in the UGT2B15, rs266882 in the PSA, rs10625775443 in the GNB3, rs 1800682 in the FAS, rs12052398 and rs13393577 in the ERBB4, rs181133 in the MTHFR, rs 1805087 in the MTR, rs1805355 in the MSH3, (rs60271534 in the CYP19, rs2234693 and rs9340799 in the ER-a, rs4986938 and rs1256049 in the ER-b) and single-nucleotide polymorphisms in important pathways (such as angiogenesis, androgen receptor binding site, cell signaling, folate metabolism, DNA repair, hormone synthesis and metabolism polymorphisms ) involved in prostate cancer occurrence and mechanism could serve as candidate biomarkers for the detection of PCa. The most important results of the all studied articles is summarized in Table 1 and 2. Conclusion: Several studies have been conducted on the family history of PCa. The main reason for this gathering is to inherit the involved genes. Additional studies are required to decipher precisely the gene combinations and personalize the management of prostate cancer. This article is the first comprehensive overview of genetic investigations of gene polymorphisms on PCa. in Iran.